2018
DOI: 10.4103/nmj.nmj_165_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic accuracy of rapid diagnostic test for malaria diagnosis among febrile children in Calabar, Nigeria

Abstract: Background: The WHO recommends that all cases of suspected malaria should undergo parasitological test. Currently, the parasitological test comprises the rapid diagnostic test (RDT) or the microscopy. The performance of RDT in relation to microscopy is yet to be fully comprehended. Objectives: This study evaluated the diagnostic accuracy of RDT as against the diagnosis provided by microscopy in detecting malaria parasites among febrile under-5 children. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The blood samples collected from patients must be lysed before the Plasmodium antigens being stained. RDT will indicate if the patient has malaria or not [38]. This diagnostic method is useful in rural areas as it is inexpensive and does not require expertise to perform the test [38].…”
Section: Rapid Diagnostic Test (Rdt)mentioning
confidence: 99%
See 1 more Smart Citation
“…The blood samples collected from patients must be lysed before the Plasmodium antigens being stained. RDT will indicate if the patient has malaria or not [38]. This diagnostic method is useful in rural areas as it is inexpensive and does not require expertise to perform the test [38].…”
Section: Rapid Diagnostic Test (Rdt)mentioning
confidence: 99%
“…RDT will indicate if the patient has malaria or not [38]. This diagnostic method is useful in rural areas as it is inexpensive and does not require expertise to perform the test [38]. There are various types of RDTs that can detect different antigens of Plasmodium parasites including P. falciparum and P. vivax,namelyP.…”
Section: Rapid Diagnostic Test (Rdt)mentioning
confidence: 99%
“…Data from studies in the Democratic Republic of Congo have shown that only 18% of health workers correctly reported RDT results obtained as part of an external quality assurance (EQA) programme [3]. Unacceptably high false-positive and false-negative results from RDT use have been shown in other studies [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, World Health Organization (WHO)-recommended methods for the detection of both malaria and lymphatic filariasis (LF) rely upon either the microscopic examination of blood samples or serological antigen/antibody testing [4][5][6]. While widely used and important for programmatic decision making processes [7][8][9], these approaches are dependent upon human blood sampling and considerable evidence exists demonstrating the potential for these testing methods to lead to both false-positive and false-negative results [6,[10][11][12]. While requiring more advanced infrastructure, DNA-based assays utilizing quantitative real-time polymerase chain reaction (qPCR), are able to improve upon diagnostic sensitivity and specificity of detection for these diseases [6,[13][14].…”
Section: Introductionmentioning
confidence: 99%